Influence of different type of mutations in the biochemical profile of Portuguese patients with familial hypercholesterolemia - Medeiros, A.M. (2012)
Familial Hypercholesterolemia (FH) is characterized by high levels of LDLc in plasma, accelerated atherosclerosis and increased risk of premature coronary heart disease. FH results from mutations in three genes involved in lipid metabolism: LDLR, APOB, PCSK9. It is known that FH patients’ phenotype is heterogeneous varying with different conditions. The aim of this study was to analyse the biochemical profile of patients with genetically diagnosed FH in accordance with the mutations in different genes and the different types of mutations identified in the LDLR gene to identify whether there is a correlation between these variables in Portuguese patients. Biochemical parameters, total cholesterol (TC), LDLc, HDLc, triglycerides, ApoB and ApoA of 325 patients with FH were analyzed by SPSS using ANOVA and Tukey’s test. Patients with mutations in the PCSK9 have LDLc and TC levels significantly higher than patients with mutations in the remaining two genes. There is no significant difference in these parameters between patients with mutations in LDLR and APOB genes, although all values are higher in patients with mutations in the LDLR. Patients with nonsense mutations in the LDLR gene present values of TC, LDL and ApoB statistically higher than in patients with missense mutations. The comparison between the other categories showed no significant changes in biochemical parameters. Patients with mutations in the PCSK9 have a more severe phenotype (based on biochemical and cardiovascular profile) than patients with mutations in LDLR and APOB genes. The type of mutation (in different genes or different mutations in LDLR) is associated with different phenotypes and so is important in determining cardiovascular risk in FH patients.